Análise estatística de parâmetros elétricos em usinas sucroalcoleiras do centro-oeste paulista - Halmeman, Maria Cristina Rodrigues; Gabriel Filho, Luís Roberto Almeida [UNESP]; Seraphim, Odivaldo José; Perea, Luiz Antonio; Halmeman, Radames Juliano (EIA Energy in Agriculture, 2013)
The industry of sugar cane has become an important contributor to the generation of electricity in Brazil. Currently there are 434 sugar and ethanol plants operating in the country, 23% of the total export electricity to the National Integrated System (SIN), the state of São Paulo has 182 plants and 30% of them export energy to the SIN. The objective of this study is to compare parameters of electrical efficiency in the sugar and alcohol industry. For the study, three plants localized in the midwest region of Sao Paulo state with great potential for production and exporting bioenergy were chosen. Five energy analyzers LANDYS + GYR SAGA were used for measure the electrical parameters. The variables studied were energy consumption (C) and power factor (PF). For the statistical analysis it was adopteda randomized block design in a factorial 3 5composed of three companies and five sectors of energy consumption,in which: reception(1), milling (2), boiler (3), supporting activities / juice treatment (4), and distillation (5), totaling 15 treatments. Each group comprised 192 repetitions (48 hours 4 measurements per hour). It was concluded that there is no interest for the plans to fix the FP and reach a value 0.92, which is considered the ideal power factor.This,because the plants generate their own energy and are not penalized. Regarding the energy consumed, all sectors had significant differences. When comparingsector to sector, the plant called USB showed no significant differences in sectors 1 and 3, and the plant USC, in sectors 1 and 4. Considering the production units of this sector and selling power this type of evaluation is essential to perform this analysis, since the analyzed sectors are most important in the production of sugar and ethanol, and analyze and monitor these parameters, use and consumption energy can provide a greater supply of energy to be commercialized.

A indústria da cana-de-açúcar tornou-se um importante colaborador na geração de energia elétrica no Brasil. Atualmente há 434 usinas de açúcar e etanol em operação no país e deste total 23% exportam energia elétrica para o Sistema Integrado Nacional (SIN). No estado de São Paulo há 182 usinas e 30% delas exportam energia para o sistema. O objetivo deste trabalho é comparar parâmetros de eficiência elétrica no setor sucroalcooleiro. Para o estudo, foram escolhidas três usinas com grande potencial de produção e exportação de açúcar e etanol da região centro-oeste do estado de São Paulo. Foram utilizados, para aferição de parâmetros elétricos, cinco analisadores de energia LANDYS+GYR SAGA. As variáveis analisadas foram a energia consumida (C) e Fator de Potência (FP). Para a análise estatística, adotou-se o delineamento de blocos casualizados, em arranjo fatorial 3 5, composto das três empresas sucroalcoleiras e cinco setores de consumo energético sendo: recepção (1), moagem (2), caldeiras (3), atividades auxiliares/tratamento de caldo (4) e destilaria (5) totalizando 15 tratamentos, sendo cada grupo composto por 192 repetições (48 horas 4 aferições por hora). Conclui-se que não há uma preocupação por parte das usinas em corrigir o (FP) e atingir o valor de 0,92, que é considerado o fator de potência ideal, visto que as usinas, por gerarem sua própria energia, não são penalizadas pelas concessionárias por apresentarem valores abaixo do recomendado. Em relação à energia consumida todos os setores apresentam diferenças significativas. Na comparação setor a setor, a usina denominada USB apresentou diferenças não significativas nos setores 1 e 3 e a usina USC nos setores 1 e 4.
Statistics analyses of the electric parameters in sugar cane plants at central west of Sao Paulo State
Keywords: Power Analyzers; Power factor; Energy consumed; Analisadores de energia; Fator de potência; Energia consumida